Real estate brokers and commission: Theory and calibrations - Oz Shy (Federal Reserve Bank of Boston, 2009)
The author constructs a theoretical model to examine the effects of an inherent conflict of interest between a seller of a house and the real estate broker hired by the seller. The model is then used to calibrate the broker's commission rates that would maximize the seller's expected gain. The findings suggest that while the pressure brokers exert on sellers to reduce prices generates faster sales and hence improves social welfare, the usual commission rate of 6 percent exceeds the seller's value-maximizing rate if the sale is handled by a single agent. On the other hand, if several agents (such as the buyer's and seller's brokers and the agencies that employ these realtors) split the commission, then a 6 percent commission rate may be required to motivate the broker to sell at a high price.
Keywords: L85; 330; real estate brokers; selling a house; conflict of interest; middleman; commission; price fixing; Immobilienmakler; Immobilienmarkt; Immobilienpreis; Theorie